(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
This article discusses the impact of stigma on feminism through the approach of critical reflective inquiry. It adopts conceptualization of stigma as having social components by Link and Phelan (2001), in discussion of how stigma is created and Kleinman and Hall-Clifford’s (2009) approach on combating it. Utilizing evidence of personal experiences, I argue that stigma brings self-censorship and often refrains people from accepting their true nature. Stigmatizing feminism resulted in a generation of women alienating themselves from the concept, while still fighting for equal rights of women. The article begins with a definition of stigma, followed by a brief history of global feminism and feminism in Nepal. Then it shifts to discuss how western feminism was introduced as a stigma in Nepal and how it shaped the thought process of multiple generations, impacting the women right’s movement. I use my experience as an example of how stigma shaped my perception of feminism and how I was able to combat it. I conclude that stigma around feminism changed the discourse surrounding feminism from being a struggle for equal rights, to fight against male-privilege, thereby sidelining women from the discourse. An understanding of the inception of this narrative is important in combating the stigma.